Processing Systems Synthesis with Embedded Reliability Consideration - Orosz, Akos; Kovacs, Zoltan; Friedler, Ferenc (Computer Aided Chemical Engineering, 2018)
Reliability is one of the most important properties of processing systems, still there is no general method that is able to simultaneously considering the reliability during the design procedure. The proposed method is capable of synthesizing processing networks simultaneously taking into account reliability constraints or generating all Pareto optimal solutions for cost vs. reliability. The method is based on structural examinations and P-graph algorithms